Age of discountinuity - "Drucker, Peter.F." (London, 1969)
This book may be looked at as an 'early-warning system'. reporting discontinuities which, while still below the visible horizon, are already changing the structure and meaning of economy, polity, and society. These discontinuities, rather than the massive momentum of the apparent trends, are likely to mould and shape our tomorrow, the closing decades of the twentieth century.These discontinuities are, so to speak, our 'recent future'-both are already accomplished fact and challenge to come.
Keywords: Social change